2021
DOI: 10.1200/jco.20.03637
|View full text |Cite
|
Sign up to set email alerts
|

Neck Dissections Based on Sentinel Lymph Node Navigation Versus Elective Neck Dissections in Early Oral Cancers: A Randomized, Multicenter, and Noninferiority Trial

Abstract: PURPOSE This study aimed to compare patients with early oral cavity squamous cell carcinoma (OCSCC) (tumor category [T] 1-2, node-negative, and no distant metastasis) treated with traditional elective neck dissection (ND) with those managed by sentinel lymph node biopsy (SLNB) using survival and neck function and complications as end points. METHODS Sixteen institutions in Japan participated in the study (trial registration number: UMIN000006510). Patients of age ≥ 18 years with histologically confirmed, previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 37 publications
(44 reference statements)
2
110
0
Order By: Relevance
“…47 Patient-reported outcomes will also be explored using the European Quality of Life Five Dimension Five Level Scale Questionnaire (EQ-5D-5L). While two robust RCTs were included in our analysis that also looked extensively into shoulder morbidity and quality of life, 17,18 more studies such as the aforementioned clinical trial with larger sample sizes are needed to provide stronger evidence for SNB to be considered as a viable alternative to END for OCSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Patient-reported outcomes will also be explored using the European Quality of Life Five Dimension Five Level Scale Questionnaire (EQ-5D-5L). While two robust RCTs were included in our analysis that also looked extensively into shoulder morbidity and quality of life, 17,18 more studies such as the aforementioned clinical trial with larger sample sizes are needed to provide stronger evidence for SNB to be considered as a viable alternative to END for OCSCC.…”
Section: Discussionmentioning
confidence: 99%
“…14 Despite proven diagnostic capabilities and improved morbidity compared with END, there is limited data on survival outcomes between SNB and END. [14][15][16][17][18][19][20][21][22][23] Recently published randomized controlled trials (RCTs) by Hasegawa et al 18 and Garrel et al 17 found no survival differences between SNB and END arms. However, concerns have been raised about the a priori sample size requirements in these noninferiority trials, 24,25 and if these trials were adequately powered.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen a growing body of evidence to indicate that SNLB, with completion neck dissection where necessary, has similar patient survival outcomes as END for the management of the N0 neck in early stage OSCC. [8][9][10][11]20 Furthermore, cost and quality of life analyses appear to favour SNLB over END in these patients. 12,21,22 Given these observations, several authorities recommend SLNB as the standard of care in cT1-2 N0 OSCC, while some professional bodies recommend that all patients with this disease should have access to the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate similar survival outcomes between SLNB and END, [8][9][10][11] while emerging evidence suggests reduced morbidity in the former. 10,12 These findings have led several authorities to recommend SLNB over END in the management of T1-2 N0 OSCC.…”
mentioning
confidence: 97%
“…Only one study compared a large retrospective cohort of patients of a database from the National Cancer Data Base without pairing both groups of patients 35 . Other two multicenter prospective trials observed a non-inferiority of SLNB over END regarding recurrence free, disease speci c and overall survival, but not all patients had a longer follow-up [36][37] . Our study was the rst to evaluate the recurrence rate between SNB and END groups with a longer follow-up, with a proposal of pairing patients statistically.…”
Section: Discussionmentioning
confidence: 99%